Analysis of Heart Rate Variability in Newborns Dogs with Different Types of Delivery during the First 35 Days of Life - Corrêa, Jaqueline Valença [UNESP]; Latini, Carolina Dragone [UNESP]; Santos, Beatriz Almeida [UNESP]; Sarita Cruz Aleixo, Amanda [UNESP]; Pereira, Keylla Helena Nobre Pacífico [UNESP]; Tsunemi, Miriam Harumi [UNESP]; Machado, Luiz Henrique de Araujo [UNESP]; Lourenço, Maria Lucia Gomes [UNESP] (MDPI, 2024)
The present study aimed to evaluate the influence of the autonomic nervous system on cardiovascular function during the first 35 days of life in different types of delivery, using heart rate variability (HRV) indices. Thirty newborns were equally divided into two groups based on delivery type: eutocic delivery (EG) and emergency cesarean section (CG). Electrocardiographic evaluation was performed at birth (T0), 24 h postpartum (T1), and at 7, 14, 21, 28, and 35 days of life (T2 to T6). Physical parameters, neonatal reflexes, and Apgar scores were recorded. Over 35 days, the values of the time domain indices were higher in the GE group and increased with age. In the frequency domain, the low frequency (LF) index was higher in the CG, and the opposite occurred for the high frequency (HF) index. Since the CG presented lower HRV than the EG, it was shown that the type of delivery should be considered for the assessment of autonomic nervous system activity in neonates. Thus, as predictive factors of vitality, HRV and Apgar scores can help in the face of neonatal depression, demonstrating that delivery by emergency cesarean section can predispose newborns to delays in the autonomic influence on the heart.
Keywords: dogs; electrocardiogram; heart rate variability; neonatology; newborns